Perception of Students Towards Lecturers Teaching Engineering Courses with Industry Experience: A Case Study in Malaysia Technical University - Kartina, Johan (Elsevier, 2015)
Teaching effectively engineering lessons in class requires a good teaching skill but preparing the undergraduates especially the graduating students with employability skills is indeed a challenging task. In the context of Malaysia Technical University Network (MTUN), the graduating engineering students are expected to be good both in academics and the soft skills in particular of being ready to work as engineers. This is in line with the National Graduate Employability Blueprint 2012-2017 published by the Ministry of Higher Education Malaysia. One of the approaches of getting the knowledge of being an engineer is to learn and experience it from the engineers themselves. It is an advantage for students if the lecturer is an engineer himself preferably with a long attachment in the industry. However such experiential learning is feasible if the university lecturers have exposure to industrial experience as engineers and the students have certain level of fundamental knowledge to maximize the learning process. This paper aims to study the perception of the students to the lecturers with such engineering experience towards their learning experience. The study will adopt the quantitative research methodology. A structure survey instrument will be developed to study the students’ perception on the lecturers. The targeted respondents are among the engineering students in one of the technical universities in Malaysia. The data obtained are analyzed and commented using Excel spreadsheet on the frequency and relative importance value. The results show the students do benefit from learning with the experienced lecturers in the context of preparing them for employment as engineers. The high perception also supported by the fact that the majority of the students are planning to be engineers themselves upon graduation coupled with some experiences in the industry plus good fundamentals in academics. The findings indeed support the strategy of technical universities which are highly required to hire lecturers with industrial experience.